2022
DOI: 10.26434/chemrxiv-2022-5m8sx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Near-Atomic Resolution Structure of J-aggregated Helical Light Harvesting Nanotubes

Abstract: Function-oriented design of supramolecular self-assemblies represents a foundational goal in chemistry. Especially, chromophore self-assemblies display extreme photophysical changes from their monomers that are sensitive to the nanoscale molecular arrangements. Slip-stacked arrangements in J-aggregates lead to red shifts (>200 nm) and enhanced quantum yields. Actively introducing specific molecular arrangements using supramolecular chemistry provides a platform to tune the excitonic couplings and avail exot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…The adsorbed molecules move around on the IW surface and rotate to form patches of recovering OW (see Figure ). Within each patch, the molecules are locally ordered into a brickwork structure, consistent with the recently resolved experimental packing motif . Depending on its size, an isolated patch can move and rotate on the surface of the IW, until it encounters other patches.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The adsorbed molecules move around on the IW surface and rotate to form patches of recovering OW (see Figure ). Within each patch, the molecules are locally ordered into a brickwork structure, consistent with the recently resolved experimental packing motif . Depending on its size, an isolated patch can move and rotate on the surface of the IW, until it encounters other patches.…”
Section: Resultssupporting
confidence: 69%
“…Prior to microfluidic flash-dilution, C8S3 DWNTs are characterized by two prominent narrow absorption peaks at ∼17,000 and ∼16,700 cm –1 (Figure B), which are associated with exciton transitions in the OWs and IWs, respectively, , and are polarized parallel to the long tubular axis . Meanwhile, higher-lying transitions >17,200 cm –1 have overlapping contributions from both walls and contain both parallel and perpendicularly polarized transitions. , Cryo-TEM imaging showed that the DWNTs have outer and inner diameters of 13.5 ± 0.4 and 6.9 ± 0.3 nm, respectively, and tube lengths up to several μm, which is consistent with previous results. , …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior work on molecules 1a and 1b has shown that the two primary aggregate absorption features occur from the assembly of long double-walled nanotubes (DWNT) and the subsequent bundling of those nanotubes resulting in fibers of overlapping single-walled nanotubes. 27,[35][36][37] The DWNT produces several absorption peaks, with primary features at 599 and 589 nm, corresponding to the parallel transition of the inner and outer walls of the tube respectively. 27,38 Additionally, both the inner and outer wall show auxiliary features which have been assigned to the other parallel and perpendicular excitonic transitions, which are indicative of macroscopic exciton delocalization around each tubular structure.…”
Section: Resultsmentioning
confidence: 99%
“…We refer to these as a kinetic intermediate (KI) and bundles, though the analogous behaviour of 1a suggests that the KI are transiently formed double-walled nanotubes (vide infra). 27,35 We employed non-negative matrix factorization (NNMF), an algorithm which estimates the basis spectra corresponding to each species in the binary solution, (Fig. 1d) of the concentration series data in Fig.…”
Section: Resultsmentioning
confidence: 99%